2018
DOI: 10.1111/nep.13467
|View full text |Cite
|
Sign up to set email alerts
|

Role of renin‐angiotensin system in acute kidney injury‐chronic kidney disease transition

Abstract: Acute kidney injury (AKI) can increase the risk of developing incident chronic kidney disease (CKD). The severity, frequency and duration of AKI are crucial predictors of poor renal outcome. A repair process after AKI can be adaptive and kidney recovers completely after a mild injury. However, severe injury will lead to a maladaptive repair, which frequently progresses to nephron loss, vascular rarefaction, chronic inflammation and fibrosis. Although different mechanisms underlying AKI‐CKD transition have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 57 publications
0
28
0
1
Order By: Relevance
“…[27][28][29][30] The possible behind mechanisms include ER stress, incomplete or maladaptive tissue repair, driven fibrosis, inflammation and capillary rarefaction. 8,[31][32][33] The loss of nephron mass and the consequent nephron hyperfiltration can lead to the activation of the renin-angiotensin system, hypertension and the subsequent glomerulosclerosis. [34][35][36] Experimental models have shown that selective epithelial injury could drive capillary sparseness, interstitial fibrosis, glomerulosclerosis and CKD, substantiating a direct role for damaged TEC in disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] The possible behind mechanisms include ER stress, incomplete or maladaptive tissue repair, driven fibrosis, inflammation and capillary rarefaction. 8,[31][32][33] The loss of nephron mass and the consequent nephron hyperfiltration can lead to the activation of the renin-angiotensin system, hypertension and the subsequent glomerulosclerosis. [34][35][36] Experimental models have shown that selective epithelial injury could drive capillary sparseness, interstitial fibrosis, glomerulosclerosis and CKD, substantiating a direct role for damaged TEC in disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, consequent to altered oxygen availability, tubular injury and necrosis cause tubular dysfunction, oliguria and reduced glomerular filtration via tubulo-glomerular feedback. Thus, after an ischemic injury, the loss of nephronic mass, with remnant nephron hyperfiltration, renin-angiotensin system (RAS) activation, systemic hypertension and subsequent glomerulosclerosis have been described to pave the way from AKI to CKD [18,19,20]. Regardless of the initial insult, evidence of tubular cell loss and replacement by collagen scars and infiltrating macrophages are associated with further renal functional loss and progression towards end stage renal failure.…”
Section: Aki Is Not a Self-limiting Eventmentioning
confidence: 99%
“…Ang II also exerts direct effects on cardiomyocytes by inducing hypertrophy and apoptosis [28,29]. Interestingly, treatment with a RAAS inhibitor has been shown to protect against AKI and cardiac failure [30,31].…”
Section: Pathophysiology Of Crs-3mentioning
confidence: 99%